2017
DOI: 10.22401/jnus.17.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glass Powder on Some Mechanical Properties of Polymer Matrix Composite Material

Abstract: This research deals with the study of the effect of adding glass powder of grain size (35μm) with different volume fraction (10%, 20%) to the blend of unsaturated polyester and polyurethane using hand lay-up method, after preparing the matrix from weight fraction (90%) of Unsaturated polyester and (10%) of polyurethane. The results have shown that the addition of particles to the polymer blends lead a great extent in mechanical properties, since testing bending, Shore D hardness and impact strength. It has sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Results show a higher value for hardness shore D is (87.93 at 3%), (84.16at 0.5%) and (84.21at 3%) for GP, SF, CB respectively, compared to the hardness shore D of the neat (65). The increase in hardness values with increase weight fraction of glass powder and carbon black agree with results of Musa [6] and Flores [9]. Hardness values increased for all samples which strengthen by glass powder, silica fume, carbon black due to increased crosslinking and stacking of the unsaturated polyester matrix (which reduces the.…”
Section: Hardness Testsupporting
confidence: 85%
See 2 more Smart Citations
“…Results show a higher value for hardness shore D is (87.93 at 3%), (84.16at 0.5%) and (84.21at 3%) for GP, SF, CB respectively, compared to the hardness shore D of the neat (65). The increase in hardness values with increase weight fraction of glass powder and carbon black agree with results of Musa [6] and Flores [9]. Hardness values increased for all samples which strengthen by glass powder, silica fume, carbon black due to increased crosslinking and stacking of the unsaturated polyester matrix (which reduces the.…”
Section: Hardness Testsupporting
confidence: 85%
“…Her results have shown that the addition of particles to the polymer blends lead largely in mechanical properties it has shown that the values of young modulus, impact strength and hardness (shore D) were increase with increasing of volume fraction of glass powder. Fracture surface of the samples were examined using optical microscope with magnification (40 X) and the results showed that the nature of fracture is seems brittle fracture for all samples [6]. This work aimed to evaluate the mechanical properties (hardness, bending, impact strength, compression strength, and wear) for unsaturated polyester as a matrix with silica fume, glass powder and carbon black as reinforcement composite systems.…”
Section: Flores Et Al Studied the Influence Of Filler Structure Onto ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer composites are stronger and stiffer than their unfilled counterparts. For effective reinforcement to occur, filler particles should be small, evenly dispersed in the matrix, and has strong interfacial adhesion with the matrix [3]. Siliceous mineral fillers contain highly polar silanol (-SiOH) group which has weak interaction with nonpolar polymer matrices such as ABS and PLA.…”
Section: Introductionmentioning
confidence: 99%
“…In general, composites are stiffer and stronger than unfilled polymers. For effective reinforcement, the particles should be small, evenly distributed throughout the polymer matrix, and must form adhesive bond with the matrix [4]. Furthermore, it is expected that increasing the loading of fillers will significantly augment the material property of polymer resin.…”
Section: Introductionmentioning
confidence: 99%